Ð’Ð¸Ð·Ð½Ð°Ñ‡ÐµÐ½Ð½Ñ Ð¾ÑÐ¼Ð¾Ñ‚Ð¸Ñ‡Ð½Ð¾ Ð½ÐµÐ°ÐºÑ‚Ð¸Ð²Ð½Ð¾Ð³Ð¾ Ð¾Ð±'Ñ”Ð¼Ñƒ ÐµÐ½Ñ‚ÐµÑ€Ð¾Ñ†Ð¸Ñ‚Ñ–Ð² Ð¼Ð¸ÑˆÑ– - Ogurtsova, Viktoriya V.; Kovalenko, Svetlana Ye.; Kovalenko, Igor F.; Gordiyenko, Olga I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(1):93-97.